Pengaruh Penilaian Kinerja Terhadap Motivasi Kerja Karyawan Pada Hotel Cipta Mampang Jakarta Selatan - Isnurrini hidayat (Universitas Bina Sarana Informatika, 2018)
Performance appraisal is very important on organitation. One of the goal from performance appraisal is to increase the work motivation of the employment so it can reach the maximum work. This research to get know about the influence of performance appraisal to work motivation at Hotel Cipa Mampang Jakarta Selatan. The sampel that used are saturation sampling which are all of the 50 employed from Personnel&General Affairs, Accounting&Finance, Marketing, Front Office dan Food&Beverage and using likert scale. The research method use are : methods observation, interview, questionnaire and documentation. The calculate method that use are : test of correlation coefficient, determination coefficient, and simple linear regression equation with the computer program of SPSS 17. The result of the coefficient correlation value 0,0721 shows the relationship between performance appraisal and motivation is strong. The determination test obtained R square is equal to 0,520 or 52% of the working motivation variables, which are influenced by performance appraisal, while the remaining 48% are influenced by other factor. The test of equal regression obtained by equation Y= 8,464 + 0,807X, if the coeffient of performance appraisal is 0, then the working motivation is 8,464.